Study of the Efficacy of Moringa Oleifera Roots Applied as a Poultice in the Symptomatic Treatment of Gonarthrosis - Dossou-Yovo, Vigniako Roussaint; Osseni, Abdou Razack; Zomalheto, Zavier Cossi; Laleye, Anatole (European Scientific Journal, ESJ, 2026)
Introduction: The roots of Moringa oleifera are widely used for arthralgia. The aim of this study is to evaluate the effectiveness of a poultice made from Moringa oleifera root powder in the symptomatic treatment of gonarthrosis. Material and methods: It was a randomized, double-blind study, controlled against a placebo and against standard drug treatment in an open setting, conducted in the rheumatology department of CNHU-HKM in Cotonou. The patients included in the study had an arthritic flare at the beginning of the study. Two parallel groups were established, one group received a knee poultice containing Moringa oleifera, while the other group received a placebo poultice. The primary outcome measure was based on the calculation of the effect size for pain intensity and the secondary endpoint was the mean duration of pain recurrence. Data was processed using Epi Info software version 7.2.1.0. The Hedges statistic was used to assess the effect size between the two groups. Results: Sixty-five patients were randomized (Moringa=35, Placebo=30). The studied population was characterized by a female predominance of 90,47%, with an average age of 57.94 years. The results of the effect size calculation for pain intensity showed a standardized difference greater than 0.8 in the Moringa and Placebo groups over a duration of 2 weeks (p < 0.0001). The mean duration of pain recurrence in the Placebo group was 4.62 days after treatment discontinuation, with a range of 1 to 15 days. It was 59.11 days after treatment discontinuation in the Moringa group, with a range of 1 to 222 days. Only 5.88% of patients in the Moringa group reported adverse effects such as mild itching after removing the poultice. Conclusion: This study showed that Moringa oleifera roots could constitute a potential therapeutic alternative in flare-ups of gonarthrosis.